IMPACT DUST NOT THE CAUSE OF CRETACEOUS-TERTIARY MASS EXTINCTION - Pope K.O. (My University, 2002)
Most of the 3-mm-thick globally distributed Chicxulub ejecta layer found at the Cretaceous-Tertiary (K-T) boundary was deposited as condensation droplets from the impact vapor plume. A small fraction of this layer (<1%) is clastic debris. Theoretical calculations, coupled with observations of the coarse dust fraction, indicate that very little (<1014 g) was submicrometer-size dust. The global mass and grain-size distribution of the clastic debris indicate that stratospheric winds spread the debris from North America, over the Pacific Ocean, to Europe, and little debris reached high southern latitudes. These findings indicate that the original K-T impact extinction hypothesis—the shutdown of photosynthesis by submicrometer-size dust—is not valid, because it requires more than two orders of magnitude more fine dust than is estimated here. Furthermore, estimates of future impact hazards, which rely upon inaccurate impact-dust loadings, are greatly overstated.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая